RBP1 Recruits the mSIN3-Histone Deacetylase Complex to the Pocket of Retinoblastoma Tumor Suppressor Family Proteins Found in Limited Discrete Regions of the Nucleus at Growth Arrest - Lai, Albert (American Society for Microbiology, 2001)
Retinoblastoma (RB) tumor suppressor family pocket proteins induce cell cycle arrest by repressing transcription of E2F-regulated genes through both histone deacetylase (HDAC)-dependent and -independent mechanisms. In this study we have identified a stable complex that accounts for the recruitment of both repression activities to the pocket. One component of this complex is RBP1, a known pocket-binding protein that exhibits both HDAC-dependent and -independent repression functions. RB family proteins were shown to associate via the pocket with previously identified mSIN3-SAP30-HDAC complexes containing exclusively class I HDACs. Such enzymes do not interact directly with RB family proteins but rather utilize RBP1 to target the pocket. This mechanism was shown to account for the majority of RB-associated HDAC activity. We also show that in quiescent normal human cells this entire RBP1-mSIN3-SAP30-HDAC complex colocalizes with both RB family members and E2F4 in a limited number of discrete regions of the nucleus that in other studies have been shown to represent the initial origins of DNA replication following growth stimulation. These results suggest that RB family members, at least in part, drive exit from the cell cycle by recruitment of this HDAC complex via RBP1 to repress transcription from E2F-dependent promoters and possibly to alter chromatin structure at DNA origins.